THE EFFECTS OF LANGUAGE TEACHERS’ ATTITUDES, BARRIERS AND ENABLERS IN TEACHING 21ST CENTURY SKILLS AT CHINESE VERNACULAR SCHOOLS (Malaysian Journal of Learning and Instruction, 2022)
Purpose – The study explored the barriers and enablers faced by language teachers in teaching 21st century skills at Chinese vernacular schools. It aimed to determine the effects of teachers’ attitudes, barriers, and enablers in teaching the skills during language lessons.Method – A mixed-method design was used to achieve the two objectives of this study. Quantitative data were collected from 400 language teachers from Chinese vernacular schools, and semi-structured interviews were carried out with nine of the teachers. Barriers and enablers faced by teachers were identified through literature review, semi-structured interviews, and questionnaire surveys. Triangulation was carried out for analysis purposes. The effects among the variables were analysed through partial least squares structural equation modelling via Smart PLS 3.0.Findings – The major barriers and enablers faced by language teachers in teaching 21st century skills at Chinese vernacular schools were uncovered. Direct effects of teachers’ attitudes, barriers, and enablers on the teaching of 21st century skills were found. However, there were no significant moderating effects of barriers and enablers on their teaching. Both of these variables had stronger effects on teachers’ attitudes.Significance – With the identifications of barriers and enablers faced by language teachers at Chinese vernacular schools, more effective support and interventions can be provided to these teachers. Teacher training and professional development programmes on 21st century language teaching can also be improved by incorporating the influencing factors identified in this study.